Exploring the prospect of Varanasi city for rail-based transit-oriented devevelopment: Insights from select theories and practices - Banerjee, Iman (National Geographical Journal of India, 2021)
Transit-oriented development has emerged as an admired concept among spatial policymakers and regional planners, as it can contribute to a more feasible transportation system along with sustainable urban development practices. However, successful implementation of transit-oriented development is associated with a host of issues that are both social and economic in nature. This paper aims to throw light on the notion of rail-based transit-oriented development with a specic focus on the prospect of Varanasi city and its recently redeveloped Banaras railway station. This research is grounded on the existing literature and the information available in the public domain. The study refers to some international examples to show the implications of transit-oriented development initiatives on the fabrication of a more liveable and sustainable type of cityscape. Additionally, it takes insights from contemporary Indian initiatives that depict a well-realisation of the potential of railway stations as transit-oriented development sites, which ultimately aims to achieve the broader goal of sustainable urban and transport development throughout the entire length and width of the country.